The salamander blastema within the broader context of metazoan regeneration - Tajer, Benjamin; Savage, Aaron M.; Whited, Jessica L. (Frontiers in Cell and Developmental Biology, 2023)
Throughout the animal kingdom regenerative ability varies greatly from species to species, and even tissue to tissue within the same organism (Bely and Nyberg, 2010; Tanaka and Reddien, 2011; Zhao et al., 2016; Elchaninov et al., 2021). The sheer diversity of structures and mechanisms renders a thorough comparison of molecular processes truly daunting. Are “blastemas” found in organisms as distantly related as planarians and axolotls derived from the same ancestral process, or did they arise convergently and independently? Is a mouse digit tip blastema orthologous to a salamander limb blastema? In other fields, the thorough characterization of a reference model has greatly facilitated these comparisons. For example, the amphibian Spemann-Mangold organizer has served as an amazingly useful comparative template within the field of developmental biology, allowing researchers to draw analogies between distantly related species, and developmental processes which are superficially quite different (Spemann and Mangold, 1923; De Robertis, 2009; Zinski et al., 2018). The salamander limb blastema may serve as the best starting point for a comparative analysis of regeneration, as it has been characterized by over 200 years of research and is supported by a growing arsenal of molecular tools (Spallanzani, 1768; Bonnet, 1777; Todd, 1823; Joven et al., 2019). The anatomical and evolutionary closeness of the salamander and human limb also add value from a translational and therapeutic standpoint (Fior, 2014; Wong and Whited, 2020; Arenas Gómez and Echeverri, 2021). Tracing the evolutionary origins of the salamander blastema, and its relatedness to other regenerative processes throughout the animal kingdom, will both enhance our basic biological understanding of regeneration and inform our selection of regenerative model systems.